Recombinant human thyrotropin stimulation test in 114 dogs with suspected hypothyroidism: a cross‐sectional study. (20th December 2020) - Corsini, A.; Faroni, E.; Lunetta, F.; Fracassi, F.
Abstract : Objective: To evaluate the performance and define cut‐offs for the interpretation of a thyroid‐stimulating hormone (TSH) stimulation test with a recombinant human TSH dose of 75 μg/dog administered intravenously in dogs with suspected hypothyroidism. Materials and Methods: Cross‐sectional study. Medical records of dogs presented for suspected hypothyroidism were retrospectively reviewed. Animals were included if a TSH stimulation test with a recombinant human TSH dose of 75 μg/dog was performed and follow‐up was available. Dogs with a post‐TSH serum total thyroxine (T4) level of ≥2.2 μg/dL were considered euthyroid. Dogs with a post‐TSH T4 level of <2.2 μg/dL were classified as hypothyroid or euthyroid based on follow‐up, including response to levothyroxine supplementation. A receiver operating characteristic curve analysis was used to define the performance of the test. Results: One hundred and fourteen dogs were included. Forty were classified as hypothyroid and 74 as euthyroid. Post‐TSH T4 cut‐offs of 1.3 and 1.7 μg/dL showed sensitivities of 92.5 and 100% and specificities of 97.3 and 93.2%, respectively. Post‐TSH T4 levels of >1.7 μg/dL had a negative predictive value of 100%. Post‐TSH T4 levels of <1.3 μg/dL showed a positive predictive value of 94.9%. Area under the ROC curve for post‐TSH T4 was 0.99. Clinical Significance: A TSH stimulation test performed with a recombinant human TSH dose of 75 μg/dog is highly reliable to discriminate between hypothyroid and euthyroid dogs, even in cases of concurrent non‐thyroidal illness or administration of medications. A post‐stimulation T4 concentration of >1.7 μg/dL is suggestive of normal thyroid function.